Macroeconomic Factors Affecting Petroleum Products Export: Evidence From The Frequentist and Bayesian Regression - Noor, Haris; Rahman , Aneesur; Noor , Dr. Sana; Ansari , Mohd Kadir; Fateh , Mohd; Ahmad , Dr. Md. Firdos; Mahazabi (International Journal of Accounting and Economics Studies, 2025)
This study delves into the intricacies of India's export of petroleum products within the dynamic landscape of the Gulf Cooperation Council (GCC) countries by utilizing extensive export data. Besides this, some critical macroeconomic variables affecting India’s export of petroleum products, namely OPEC oil prices and India's economic size, which is epitomized by gross domestic product, are analyzed. The empirical analysis time frame is from 2000 to 2023. To examine linkages between the variables with their coefficient signs, this study uses autoregressive distributed lag bound testing to obtain short and long-run estimates with an error correction model and ordinary least squares. Moreover, non-frequentist Bayesian linear regression is used for validity estimations. The findings reveal that both frequentist and non-frequentist approaches justify that the OPEC oil prices and India's GDP significantly affect India’s export of petroleum products to GCC countries. Lastly, diagnostic tests are applied to check stability and robustness in both frequentist and non-frequentist Bayesian regression.
Keywords: ARDL, Bayesian Regression, OPEC, OLS, Petroleum Products